Meaning, expression, and thought - Davis, Wayne A., 1951- (Cambridge studies in philosophy., 2003)
This philosophical treatise on the foundations of semantics is a systematic effort to clarify, deepen, and defend the classical doctrine that words are conventional signs of mental states, principally thoughts and ideas, and that meaning consists in their expression.